Training management system based on process safety management - Natasha, Azmi (2018)
There are many accidents happened in process industries that used highly hazardous chemical. One of the factors of accidents happen is because of inadequate training of employees. The training management system that complied with 29 CFR 1910.119(g) has been developed. This system allows users to manage and track information, documentations and required actions regarding their trainings. Besides, it provides a basis for gap analysis to be carried out. The framework was developed as a guide for the employer to manage the training in a systematic ways. Implementation of this system could help an organization to arrange their training program and ensure the competency of plant personnel as intended that could prevent and minimize catastrophic accidents in. By developing this system, it is easy for end users to know how much the percentage of compliance of training program in an organization. Moreover, the system could be better in future with additional element of others in PSM standard.